Effectiveness of Eucalyptus camaldulensis Leaves Oil in Upregulating exoU expression in Pseudomonas aeruginosa - Jaddoa, Nihad T. M.; AL-Sheikhly, Mahmood A. H.; Aldobaissi, Israa A.M.; Al-Mathkhury, Harith J. F. (Iraqi Journal of Science, 2024)
Results of the current study demonstratedthat out of eighty-three isolatesof Pseudomonas aeruginosa,only twenty-five isolateswere resistant to five different antibiotics (of different classes) that were consequentlyconsideredmultidrug resistant isolates.These isolates developed variable susceptibility toward Eucalyptuscamaldulensisleavesoil (ECO). GC-MS analysis of ECOrevealed that the aromatic oil eugenol is the major constituent.However, the most frequent MIC was 0.39 µg/ml, while the lowest frequent MIC was 3.125 µg/ml.Moreover, this oil at ½ MIC (0.195µg/ml) increased the gene expression of exoU. Itis concluded from the outcomes of the studythat ECOmay cause severe damagewhen used to treat infections caused by P. aeruginosa.